Analisis Interpretasi Karya Arahmaiani Yang Berjudul ‘Do Not Preventthe Fertility Of The Mind’ - Rasha Nadin (VisArt: Jurnal Seni Rupa dan Design, 2025)
This article analyzes Arahmaiani's artwork "Do Not Prevent the Fertility of the Mind" (1997-2014-2018) with an interpretive approach and using feminist art theory, exploring symbolic representations of women's autonomy over their bodies and minds. The artwork features a combination of elements such as sanitary napkins, blood in vials, and a photograph of the artist wearing a nurse's outfit while holding a contraceptive and scissors. These symbols challenge social norms that regulate women's roles, emphasizing the importance of women's control over their reproductive health and intellectual freedom. Based on feminist principles, this article highlights how Arahmaiani's artwork critiques patriarchal structures that limit women's agency. By analyzing these elements in the context of feminist discourse, this article emphasizes the importance of women's intellectual and physical freedom, and encourages society to reconsider the limitations imposed on them. This analysis contributes to the understanding of the role of feminist art in changing narratives about gender, autonomy, and identity.